A year of H2 measurements at Weybourne Atmospheric Observatory, UK - Grant L. Forster; William T. Sturges; Zoe L. Fleming; Brian J. Bandy; Stefan Emeis (Tellus: Series B, Chemical and Physical Meteorology, 2012)
We present a year-long high precision time series of atmospheric molecular hydrogen (H2) measured at the UK North Sea coast from March 2008 to February 2009. We observed a pronounced seasonal cycle in H2 with mean values in late winter/early spring ~40 ppb higher than those in late summer/early autumn. Background-subtracted molar H2/CO ratios (ΔH2/ΔCO) averaged 0.35±0.002 for all data combined and 0.25±0.002 when ΔH2 was above 10 ppb. The ΔH2/ΔCO ratio was highest in summer, possibly as a result of larger photochemical production. Using simultaneous measurements of ozone, we estimated the deposition velocity of H2 during nocturnal inversion events to average 3.5±0.7×10−4 m s−1 for June 2008 and 1.9±1×10−4 m s−1 for July 2008, in good agreement with other reported estimates. In May 2008, we observed an episode of exceptionally clean air being transported from the tropics but arriving from the north, in which H2 was slightly elevated indicating minimal surface loss. On another occasion with south-easterly winds, we believe we detected emissions from H2 production facilities in the near-continent characterised by H2 mixing ratios reaching 1450 ppb.